Common mode voltage mitigation in a three phase 21-level asymmetrical inverter fed induction motor - Narayana, Mamatha; Rajappa, Ramesh Honnappanahalli (Institute of Advanced Engineering and Science, 2024)
For many years, numerous high-power applications have been found to cause mechanical damage to the rotating shaft. This research demonstrates that common mode voltage (CMV), which causes common mode leakage currents to flow into the motor bearings and spinning shaft, is one of the main contributing factors to mechanical shaft failures. By applying a carrier based Sinusoidal pulse width modulation (PWM) approach in conjunction with a proportional integral or PI controller technique in the feedback, the study aims to reduce leakage currents by mitigating the common mode voltages induced by the inverter output asymmetry. To accomplish the stated goal, an asymmetrical inverter architecture with a 21-level is employed. The literature emphasized the trade-off between total harmonic distortion (THD) and CMV, which is attempted to be kept well below IEEE's allowable bounds. The system stability is verified and proved by plotting the bode diagram.